Anomalous left coronary artery arising from the pulmonary artery in infancy: is early operation better?. Issue 6 (December 1988) - Kakou Guikahue, M; Sidi, D; Kachaner, J; Villain, E; Cohen, L; Piechaud, J F; Le Bidois, J; Pedroni, E; Vouhe, P; Neveux, J Y
Abstract : From January 1975 to January 1987, 21 consecutive infants aged less than six months (mean (SD) 2.6 (1.2] were admitted with anomalous origin of the left coronary artery from the pulmonary artery. In the first 12 patients, who were seen up to 1982, operation was performed after the age of one year (mean (SD) 29 (29) months) (group 1). The next nine infants, seen from 1983 to 1987, had their operations within a few weeks of the onset of symptoms (mean (SD) age 4.8 (1.4) months) (group 2). In group 2 the left coronary artery was relocated into the aorta, whereas in group 1 there was additional resection of the left ventricular wall or mitral valvoplasty or both. At presentation there were no differences in age, clinical condition, heart enlargement, and echocardiographic left ventricular dysfunction between groups 1 and 2. Seven of the 12 patients in group 1 died, five while they were awaiting operation (three died suddenly at home) and two at operation. The five survivors are doing well 6.4 (3.1) years after operation with normal left ventricular function which improved slowly over several months after operation. Two of the nine patients in group 2 died; both deaths occurred at or soon after operation. The seven survivors are doing well 1.8 (0.9) years after operation. In three, left ventricular function recovered within three weeks; and there was even partial or total regression of the Q waves in the supposedly necrotic areas. In the remaining four the pattern of improvement in left ventricular function resembled that in group 1. Operation should be undertaken early in infants with anomalous left coronary artery arising from the pulmonary artery because the procedure is relatively safe, prevents a high natural mortality, and offers a better chance of a faster recovery of left ventricular function.